# Solve for x

how do i solve x for (2/x+3)=9/4=5 and none is in parenthesis.

Are you sure that's copied right? 9/4 isn't equal to 5.
dr.j
23 August 2013
The question isn't typed write there are four conditions (2/x+3)=9/4=5 Solution:2/x+3=9/4=5 2/x + 3 - 3 =
quick_help_desk
23 August 2013
Solution of i).:((2)/(x)+3)+(9)/(4)=5Combine (2)/(x)+3 into a single expression by finding the least common denominator (LCD). The LCD of (2)/(x)+3 is x.((3x+2)/(x))+(9)/(4)=5Multiply each term by a factor of 1 that will equate all the denominators. In this case, all terms need a denominator of 4x. The ((3x+2))/(x) expression needs to be multiplied by ((4))/((4)) to make the denominator 4x. The (9)/(4) expression needs to be multiplied by ((x))/((x)) to make the denominator 4x.(3x+2)/(x)(4)/(4)+(9)/(4)(x)/(x)=5Multiply the expression by a factor of 1 to create the least common denominator (LCD) of 4x.((3x+2)(4))/(4x)+(9(x))/(4x)=5The numerators of expressions that have equal denominators can be combined. In this case, ((3x+2)(4))/(4x) and ((9(x)))/(4x) have the same denominator of 4x, so the numerators can be combined.((3x+2)(4)+(9(x)))/(4x)=5Combine all similar expressions in the polynomial.(21x+8)/(4x)=5Since the variable is in the denominator on the left-hand side of the equation, this can be solved as a ratio. For example, (A)/(B)=C is equivalent to (A)/(C)=B.(21x+8)/(5)=4xMultiply each term in the equation by 5.21x+8=20xMove all terms not containing x to the right-hand side of the equation.x+8=0Since 8 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 8 from both sides.x=-8
quick_help_desk
23 August 2013
The question isn't typed write there are four conditions i). (2/x+3)+9/4=5ii). (2/x+3)-9/4=5iii). (2/x+3)=9/4+5iv). (2/x+3)+9/4-5
quick_help_desk
23 August 2013
Solution of ii).:((2)/(x)+3)-(9)/(4)=5Combine (2)/(x)+3 into a single expression by finding the least common denominator (LCD). The LCD of (2)/(x)+3 is x.((3x+2)/(x))-(9)/(4)=5Multiply each term by a factor of 1 that will equate all the denominators. In this case, all terms need a denominator of 4x. The ((3x+2))/(x) expression needs to be multiplied by ((4))/((4)) to make the denominator 4x. The -(9)/(4) expression needs to be multiplied by ((x))/((x)) to make the denominator 4x.(3x+2)/(x)(4)/(4)-(9)/(4)(x)/(x)=5Multiply the expression by a factor of 1 to create the least common denominator (LCD) of 4x.((3x+2)(4))/(4x)-(9(x))/(4x)=5The numerators of expressions that have equal denominators can be combined. In this case, ((3x+2)(4))/(4x) and -((9(x)))/(4x) have the same denominator of 4x, so the numerators can be combined.((3x+2)(4)-(9(x)))/(4x)=5Combine all similar expressions in the polynomial.(3x+8)/(4x)=5Since the variable is in the denominator on the left-hand side of the equation, this can be solved as a ratio. For example, (A)/(B)=C is equivalent to (A)/(C)=B.(3x+8)/(5)=4xMultiply each term in the equation by 5.3x+8=20xMove all terms not containing x to the right-hand side of the equation.-17x+8=0Since 8 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 8 from both sides.-17x=-8Divide each term in the equation by -17.x=(8)/(17)
quick_help_desk
23 August 2013
Solution of iii).((2)/(x)+3)=(9)/(4)+5Combine (2)/(x)+3 into a single expression by finding the least common denominator (LCD). The LCD of (2)/(x)+3 is x.((3x+2)/(x))=(9)/(4)+5Remove the parentheses around the expression ((3x+2))/(x).(3x+2)/(x)=(9)/(4)+5Combine 5+(9)/(4) into a single expression by finding the least common denominator (LCD). The LCD of 5+(9)/(4) is 4.(3x+2)/(x)=(29)/(4)Since there is one rational expression on each side of the equation, this can be solved as a ratio. For example, (A)/(B)=(C)/(D) is equivalent to AD=BC.(3x+2)4=29xMultiply (3x+2) by 4 to get 4(3x+2).4(3x+2)=29*xMultiply 29 by x to get 29x.4(3x+2)=29xMultiply 4 by each term inside the parentheses.12x+8=29xMove all terms not containing x to the right-hand side of the equation.-17x+8=0Since 8 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 8 from both sides.-17x=-8Divide each term in the equation by -17.x=(8)/(17)
quick_help_desk
23 August 2013
Solution of iv).:((2)/(x)+3)=(9)/(4)-5Combine (2)/(x)+3 into a single expression by finding the least common denominator (LCD). The LCD of (2)/(x)+3 is x. ((3x+2)/(x))=(9)/(4)-5Remove the parentheses around the expression ((3x+2))/(x). (3x+2)/(x)=(9)/(4)-5Combine -5+(9)/(4) into a single expression by finding the least common denominator (LCD). The LCD of -5+(9)/(4) is 4. (3x+2)/(x)=-(11)/(4)Since there is one rational expression on each side of the equation, this can be solved as a ratio. For example, (A)/(B)=(C)/(D) is equivalent to AD=BC.(3x+2)4=-11xMultiply (3x+2) by 4 to get 4(3x+2).4(3x+2)=-11*xMultiply -11 by x to get -11x.4(3x+2)=-11xMultiply 4 by each term inside the parentheses.12x+8=-11xMove all terms not containing x to the right-hand side of the equation.23x+8=0Since 8 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 8 from both sides.23x=-8Divide each term in the equation by 23.x=-(8)/(23)
quick_help_desk
23 August 2013
2/X +3 = 9/4     2/X=9/4-32/X=-3/4X=-4*2/3=-8/3ALSO 2/X+3=52/X=5-3=2X=2/2=1
bipan
01 September 2013
2/x+3 = 9/4 +52/x + 3 -3 = 9/4 +5 -32/x = 9/4+22/x = (9 + 2 * 4)/42/x = 17/44 * 2/x = 178/x = 17 x * 8/x = 17 * x8 = 17 xx = 8/17
elrech60
23 September 2013